Operationalizing Islamic Values and Humanism in the Merdeka Curriculum: Implementation Barriers, Stakeholder Strategies, and Policy Pathways - Anas Fadlol Firdaus (Global Journal of Islamic Education, 2025)
While the integration of Islamic values and humanism into the Merdeka Curriculum has gained widespread philosophical endorsement, empirical evidence reveals persistent implementation gaps at the school level. This study adopts a critical policy analysis perspective to examine how the synergy between Islamic ethics (justice, honesty, responsibility) and humanistic principles (learner autonomy, dignity, holistic development) is operationalizedor obstructed within Indonesia’s educational reform. Employing a systematic literature review (SLR); interactive data analysis (collection, reduction, display, conclusion drawing), this research identifies key barriers: fragmented teacher understanding of value integration, underdeveloped humanistic pedagogies, weak cross-sector collaboration, and a tendency to reduce the Merdeka Curriculum to administrative flexibility rather than cultural transformation. The findings demonstrate that although the Merdeka Curriculum provides a robust philosophical and practical foundation for character education, the integration of Islamic and humanistic values remains superficial in many classrooms, leaving moral degradation indicators (bullying, drug abuse, student brawls) largely unaddressed. The implications reveal a critical gap between policy intention and classroom reality. Consequently, this study proposes six actionable strategies: (1) integrative curriculum mapping that embeds Islamic values into competency-based learning outcomes; (2) mandatory teacher professional development on humanistic learning theories; (3) Islamic-value-infused Pancasila Student Profile projects; (4) holistic education frameworks; (5) tripartite collaboration among schools, families, and communities; and (6) continuous policy evaluation using mixed-methods research. These recommendations offer policymakers and educators a pathway to transform philosophical ideals into measurable character outcomes, thereby addressing the moral crisis among Indonesian youth.